Pseudomonads as Health Hazard in Home Indeustrial Houses, Hospitals and Private Clinics; Herbal Aerosols and 1,4,-Naphthaaquinones as Effective Inhibitors - Poul, B.N.; Vakil, J.R. (Asian Journal of Chemistry, 2010)
Pseudomonads are ubiquitous bacteria, found on plants, animals,men and women and their surrounding environment. In the recentyears it has been found that, air conditioning units are responsiblefor Pseudomonas causing serious contaminating problems in home,hospitals, industrial houses, food processing plants and cold storage,poultry, meat and fish cold storages and primary clinics. The presentstudy is a brief report of their isolation, purification, identificationand characterisation by microbiological screening and standardidentification by available biochemical immunological methods.